2022
DOI: 10.3390/nano12183114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Treatment on Photoluminescence and Morphology of InGaN Multiple Quantum Wells

Abstract: In this paper, the photoluminescence (PL) properties and surface morphology of InGaN/GaN multiple quantum well (MQW) structures with the hydrogen (H2) heat treatment of InGaN are investigated to elucidate the effect of hydrogen on the structure and surface of the MQWs. The experimental results show that the H2 heat treatment on the as-grown MQWs may lead to the decomposition of InGaN and the formation of inhomogeneous In clusters. The atomic force microscope (AFM) study indicates that although the surface roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As the hydrogen flow rate increases, the enhanced diffusion of Ga atoms plays a dominant role, which is beneficial in enhancing the 2dimensional growth and suppresses the formation of new pits especially for small pits that begin to grow in last few quantum wells but has little effect on large V-pits that have already formed before MQWs [19], [20]. Moreover, the hydrogen remove the In-rich clusters from the MQWs, therefor reducing stress accumulation may also played a significant role [12]. According to the Table I, the density and size of large V-pits of two samples are almost the same, but the absence of small V-pits in sample 2 is the major difference and their impact and effect on the MicroLEDs performance will be revealed in below discussion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the hydrogen flow rate increases, the enhanced diffusion of Ga atoms plays a dominant role, which is beneficial in enhancing the 2dimensional growth and suppresses the formation of new pits especially for small pits that begin to grow in last few quantum wells but has little effect on large V-pits that have already formed before MQWs [19], [20]. Moreover, the hydrogen remove the In-rich clusters from the MQWs, therefor reducing stress accumulation may also played a significant role [12]. According to the Table I, the density and size of large V-pits of two samples are almost the same, but the absence of small V-pits in sample 2 is the major difference and their impact and effect on the MicroLEDs performance will be revealed in below discussion.…”
Section: Resultsmentioning
confidence: 99%
“…R. Czernecki, et al reported that the H2 flow reduced the indium concentration and thickness of the QWs and increase the thickness of the barriers [11]. However, Wu et al reported that the MQWs under H2 treatment has a lower EQE, while the forward and reverse currents will be reduced [12]. Such different results reported may be due to the different H2 flow rate in the carrier gas or different growth processes of the QWs.…”
Section: Introductionmentioning
confidence: 99%